2020
DOI: 10.21873/invivo.11931
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intraoperative Blood Loss on the Survival of Patients With Stage II/III Pancreatic Cancer

Abstract: Background: Pancreatic cancer is a fatal disease with a poor prognosis. Pancreatic cancer is often unresectable at the time of diagnosis, so the analysis of risk factors in patients with indications for surgery is important. We investigated the impact of intraoperative blood loss (IBL) on survival and recurrence in patients with stage II/III pancreatic cancer after curative surgery. Patients and Methods: This study included 76 patients who underwent curative surgery for stage II/III pancreatic cancer between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In hepatocellular carcinoma, Katz et al reported increased IBL during hepatic resection to be an independent prognostic factor for tumor recurrence and death (10). In pancreatic cancer, Tamagawa et al showed that IBL ≥1,000 ml was an independent risk factor for poor OS and DFS, as well as postoperative morbidity, in patients with stage II/III pancreatic cancer who underwent radical surgery (17). Nagai et al also reported that IBL was a prognostic determinant of survival after surgery for pancreatic cancer and that operative blood loss can be used to stratify the risk of pancreatic cancer mortality (7).…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, Katz et al reported increased IBL during hepatic resection to be an independent prognostic factor for tumor recurrence and death (10). In pancreatic cancer, Tamagawa et al showed that IBL ≥1,000 ml was an independent risk factor for poor OS and DFS, as well as postoperative morbidity, in patients with stage II/III pancreatic cancer who underwent radical surgery (17). Nagai et al also reported that IBL was a prognostic determinant of survival after surgery for pancreatic cancer and that operative blood loss can be used to stratify the risk of pancreatic cancer mortality (7).…”
Section: Discussionmentioning
confidence: 99%
“…Hiroshi et al also reported that increased intraoperative blood loss in patients undergoing curative resection of stage II/III pancreatic cancer was an independent risk factor for overall and recurrence-free survival in a retrospective study. 26 Operative blood loss in curative surgeries for other digestive carcinomas including hepatocellular carcinoma, gastric cancer and colorectal cancer has also been correlated with cancer recurrence. [27][28][29][30][31] Increased operative blood loss is closely related to allogeneic blood transfusion, which may cause tumor cell spreading due to downregulation of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Combined organ resection is often associated with extensive lymphadenectomy, more surgical incisions, more blood loss, and prolonged operation time, which may impair patients’ immunity and increase the risk of postoperative complications. It has been reported that the overall survival rate of patients undergoing radical gastrectomy for gastric cancer is influenced by the volume of intraoperative blood loss [33–35] . Therefore, indications for combined organ resection need to be evaluated carefully, and potential new surgical methods to reduce the incidence of anastomotic leakage after combined organ resection should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the overall survival rate of patients undergoing radical gastrectomy for gastric cancer is influenced by the volume of intraoperative blood loss. [33][34][35] Therefore, indications for combined organ resection need to be evaluated carefully, and potential new surgical methods to reduce the incidence of anastomotic leakage after combined organ resection should be explored.…”
Section: Discussionmentioning
confidence: 99%